2017
DOI: 10.1080/10803548.2017.1322832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the controlled grip force exertion tasks associated with age, gender, handedness and target force level

Abstract: The results of this study could be used for hand function evaluation guidelines. In addition, this study could be used as a tool for physiotherapy to improve hand function and prevent its decline in elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…There was no significant difference of the mean values of the non-dominant side between both groups. Choi et al [27] said that there is a decrease in hand function based on aging was more significant in females than males. This contradicted to our result of the current study that indicated by the independent t test, there were no significant differences (p>0.05) in the mean values of age.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference of the mean values of the non-dominant side between both groups. Choi et al [27] said that there is a decrease in hand function based on aging was more significant in females than males. This contradicted to our result of the current study that indicated by the independent t test, there were no significant differences (p>0.05) in the mean values of age.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the grip strengths exerted by the former and the latter groups were 18.2-54.6N and 28.1-84.4N, respectively, in the low demand value phase (5%-15% of MVC), whereas that in the high demand value phase (15%-25% of MVC) were 54.6-91.0 N and 84.4-140.7 N, respectively. Choi et al [25] reported that the effect of grip strength on the error between pursuing the target (demand value) and the exerted value was larger at low demand value phase, but small at demand values over 15% MVC. The hypothesis of this study was not supported in the high demand value phase.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for using the pressure sensors as part of a 'return © 2018 Occupational Therapy Australia 3D PRINTED SENSORS FOR HAND STRENGTH ASSESSMENT to work' threshold or for biofeedback in rehabilitation warrants further investigation. It could also be worthwhile examining the effect of multifinger force production using the pressure-sensing fabric, as stipulated in a recent publication by Choi, Kim, Lee, Lee and Kong (2017).…”
Section: Recommendationsmentioning
confidence: 99%